Low-density lipoprotein cholesterol levels and in-hospital bleeding in patients with atrial fibrillation: findings from CCC-AF project - Tong, Xue-ying; Lin, Jing; Sun, Zhao-qing; He, Qian; Zhan, Yu; Jiang, Chen-Xi; Tang, Ri-bo; Sang, Cai-hua; Ning, Man; Jia, Chang-qi; Feng, Li; Wang, Wei; et al. (Frontiers in Cardiovascular Medicine, 2025)
Background and aimsEmerging evidence indicates a relationship between low-density lipoprotein cholesterol (LDL-C) levels and bleeding. However, data regarding the relationship between LDL-C levels and bleeding events in patients with atrial fibrillation (AF) remain unfilled. This study is aimed to examine the relationship between LDL-C levels and the risk of in-hospital bleeding in patients with AF.Methods and resultsIn this multi-centered observational study, 25,380 patients with AF were enrolled; 14,071 (55.4%) and 11 309 (44.6%) were men and women, respectively, and the mean age was 69.51 ± 11.88 years. After adjusting for covariates, with LDL-C ≥ 70 mg/dl as the reference, LDL-C < 70 mg/dl was associated with a higher risk of any bleeding event [adjusted odds ratio [aOR]: 1.63, 95% confidence interval [CI]: 1.12–2.35; P = 0.009], major bleeding events (aOR: 1.48, 95% CI: 0.99–2.20; P = 0.05), and gastrointestinal bleeding events (aOR: 2.11, 95% CI: 1.27–3.50; P = 0.004) in the multivariate logistic regression model. The restricted cubic spline model showed an L-shaped relationship for bleeding events, with a higher risk at lower LDL-C levels. The nonlinear relationship between LDL-C levels and the risk of bleeding persisted among the subgroups.ConclusionsThis nationwide and multi-centered AF registry study found an L-shaped relationship between LDL-C levels at admission and in-hospital bleeding events, with a greater risk at lower LDL-C levels. Further studies are needed to establish LDL-C as a factor for risk stratification and management of bleeding events in patients with AF.Clinical Trial Registration[http://www.clinicaltrials.gov], identifier [NCT02309398].